Silibinin-modified Hydroxyapatite coating promotes the osseointegration of titanium rods by activation SIRT1/SOD2 signaling pathway in diabetic rats - Tao, Zhou-Shan; Wang, Hai-Sheng; Li, Tian-Lin; Wei, Shan (Journal of materials science. Materials in medicine, 2022)
The purpose of this study is to investigate the role of Silibinin (SIL)-modified Hydroxyapatite coating on osseointegration in diabetes in vivo and in vitro and explore the mechanism of osteogenic differentiation of MC3T3-E1. RT-qPCR, Immunofluorescence, and Western blot were used to measure the expression level of oxidative Stress Indicators and osteogenic markers proteins. Moreover, CCK-8 assay was conducted to detect cell viability in hyperglycemia. Alizarin red staining and alkaline phosphatase staining were used to examine osteogenic function and calcium deposits. The diabetic rat model receive titanium rod implantation was set up successfully and Von-Gieson staining was used to examine femoral bone tissue around titanium rod. Our results showed that intracellular oxidative stress in hyperglycemia was overexpressed, while FoxO1, SIRT1, GPX1, and SOD2 were downregulated. SIL suppressed oxidative stress to promote osteogenic differentiation. Additionally, it was confirmed that SIL promoted osteogenic differentiation of MC3T3-E1 and obviously restored the osseointegration ability of diabetic rats. Further study indicated that SIL exerted its beneficial function through activation SIRT1/SOD2 signaling pathway to restore osteoblast function, and improved the osseointegration and stability of titanium rods in vivo. Our research suggested that the SIL-modulated oxidative Stress inhibition is responsible for the activation of the process of osteogenic differentiation through activation SIRT1/SOD2 signaling pathway in hyperglycemia, providing a novel insight into improving prosthetic osseointegration in diabetic patients. Hyperglycemia impaired the activity and function of MC3T3-E1 and inhibits bone formation by up-regulating intracellular ROS levels through inhibition of SIRT1/SOD2 signaling pathway. Local administrator SIL can improve the activity and function of osteoblasts and enhance osseointegration by reducing intracellular ROS through activation of SIRT1/SOD2 signaling pathway in DM rat models.